Perceived racism or racial discrimination and the risk of adverse obstetric outcomes: a systematic review - Pereira, Glaucia Miranda Varella; Pimentel, Veronica Maria; Surita, Fernanda Garanhani; Silva, Amanda Dantas; Brito, Luiz Gustavo Oliveira (São Paulo Medical Journal, 2022)
BACKGROUND: Racial disparities are differences among distinct subgroups of the human species; biologically, there are no scientifically proven reasons for them to exist. OBJECTIVE: To assess the impact of racism or racial discrimination on obstetric outcomes. DESIGN AND SETTING: Systematic review conducted at a tertiary/academic hospital. METHODS: The Cochrane Library, SCOPUS/EMBASE, PubMed, Web of Science and ClinicalTrials.gov data- bases were searched from inception to June 2020. Studies presenting any type of racial discrimination, or any manifestation of racism that was perceived by women of any age in an obstetric scenario were included. Studies that only assessed racial disparities without including direct racism were excluded. The secondary outcomes evaluated included quality of antenatal care, intra and postpartum care, preterm birth and birthweight. The Risk of Bias In Non-randomized Studies - of Interventions (ROBINS-I) scale was used to assess the quality of evidence from non-randomized studies. RESULTS: A total of 508 records were retrieved and 29 were selected for qualitative synthesis. No meta-analysis could be performed due to the high heterogeneity across studies. Perceived racism was associated as a risk factor in 7/10 studies focusing on pregnancy and postpartum maternal outcomes, five studies on preterm birth, one study on small for gestational age and two studies on low birthweight. Overall, among the 29 studies, the risk of bias was classified as moderate. CONCLUSIONS: Perceived racism presented an association with poor obstetric outcomes. Anti-racist measures are needed in order to address the problems that are causing patients to perceive or experience racism. SYSTEMATIC REVIEW REGISTRATION: PROSPERO database, CRD42020194382